Regulation of T Cell Signaling and Function by Cbl-b - Langdon, Wallace Y.; Thien, Christine B.F. (Current Immunology Reviews (Discontinued), 2007)
The activation of intracellular signaling pathways by the engagement of ligands with cell-surface receptors is a key event in determining the fate and function of cells. While these outcomes are primarily determined by the nature of the ligand and its receptor, proteins that negatively regulate the strength and duration of these signals are also critical components in this process. In recent years the E3 ubiquitin ligases c-Cbl and Cbl-b have emerged as prominent negative regulators of signaling responses initiated from antigen receptors on thymocytes and T cells respectively. In this review we focus on the role of Cbl-b in regulating T cell signaling and function and update new and exciting findings relating to Cbl-b deficient T cells that promote the rejection of tumors.
Keywords: Cbl proteins